Фізіологічні кореляти при виконанні фізичних вправ у моряків - Мавед, О.О. (Актуальні проблеми транспортної медицини, 2007)
Работа посвящена вопросам усовершенствования методики и медицинских критериев при выполнении физических упражнений моряками в режиме свободного времени на морских судах в период плавания. В динамике занятий физическими упражнениями наблюдаются позитивные изменения психофизиологических, физических показателей, которые коррелируют с увеличением статической выносливости, уменьшением ЧСС в конце рабочего периода, а также через 6 месяцев вы полнения физических упражнений. The work is devoted to questions of correlation to medical criteria of performance of physical exercises by seamen in a regimen of free time mode on sea vessels during navigation. In dynamics of employment by physical exercises it is observed positive changes of psychophysiological, physical parameters which correlate with response rate augmentation, decrease of fatigability, an animal force augmentation and processing rate of the mental information and also state of health improvement, activity, mood in the extremity of the working period and also in 6 months of performance of physical exercises. Dynamics of anthropometric, psychophysiological parameters under the influence of exercises stresses of faces at the age of after 40 years has proved greater efficiency of actions compared with similar data of faces age fill 40 years.